Substance Addiction in Adolescents: Influence of Parenting and Personality Traits - Irene Escamilla; Nerea Juan; Ana Benito; Francisca Castellano-García; Francesc Rodríguez-Ruiz; Gonzalo Haro (Brain Sciences, 2024)
Background: Substance use in adolescents has been separately related to personality traits and parental socialization styles; in this study, our objective was to study these variables in an integrated way. Methods: A cross-sectional observational study was conducted in five institutes in a final sample of 331 students, excluding those with gaming disorder. The sample was stratified into three subgroups: ‘no addiction’, ‘low risk’, and ‘high risk’ of Substance Use Disorders (SUD). Results: 12.9% of the adolescents presented a low risk of SUD, while 18.3% showed a high risk, with both being older (F = 9.16; p < 0.001) than the no addiction group. Adolescents with high risk scored lower in control and structure variables and higher in maternal and paternal indifference factors. Non-addicted subjects presented higher scores in conscientiousness, extraversion, and agreeableness and lower scores in neuroticism. The probability of SUD increased with age (OR = 2.187; p = 0.022), sensation seeking (OR = 1.084; p < 0.001), and neuroticism (OR = 1.049; p = 0.042), while conscientiousness was a protective factor (OR = 0.930; p = 0.008). Conclusions: These results reflect that personality traits are directly related to the development of substance abuse in adolescents.